Artificial macrocycles as IL-17A/IL-Web: 17RA antagonists. Issue 1 (15th November 2017) - Wang, Wenjia; Groves, Matthew R.; Dömling, Alexander
Abstract : Interleukin 17(A) is a pro-inflammatory cytokine involved in several auto-immune and inflammatory diseases. Abstract : Interleukin 17(A) is a pro-inflammatory cytokine involved in several auto-immune and inflammatory diseases. Current antagonists against IL-17(A) or its receptor (IL-Web:17RA ) that show efficacy in clinical trials are monoclonal antibodies (mAbs). However, recently designed artificial macrocycles are potent IL-17A/IL-; Web:17RA antagonists. Based on co-crystal structures, a better understanding of the biological activity and SAR of the macrocycles has been gained, demonstrating that they can compete with mAbs for difficult targets such as PPIs.